2022
DOI: 10.1155/2022/9184374
|View full text |Cite
|
Sign up to set email alerts
|

Coffee Drying and Processing Method Influence Quality of Arabica Coffee Varieties (Coffea arabica L.) at Gomma I and Limmu Kossa, Southwest Ethiopia

Abstract: Solar tunnel drying and semiwash processing methods are popular among coffee growers in southwestern Ethiopia. However, the effect of these processing methods on coffee quality has not been studied in detail. The objective of this study was to evaluate the effect of processing and drying methods on the quality of coffee varieties at Gomma-I and Limmu Kossa areas in the 2016/2017 growing season. Two processing methods (fully washed and semiwashed) and three drying methods (solar tunnel, artificial, and natural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 11 publications
2
10
0
Order By: Relevance
“…This farm produces specialty coffee, and all process parameters are controlled until parchment coffee is obtained. Coffee beans were manually collected as mature fruits (17)(18)(19)(20)(21)(22). Ripe coffee beans were subjected to wet fermentation for 15 hours, followed by drying for 7 -10 days in greenhouse-type experimental rooms, where temperature, relative humidity and aeration were controlled.…”
Section: Coffee Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…This farm produces specialty coffee, and all process parameters are controlled until parchment coffee is obtained. Coffee beans were manually collected as mature fruits (17)(18)(19)(20)(21)(22). Ripe coffee beans were subjected to wet fermentation for 15 hours, followed by drying for 7 -10 days in greenhouse-type experimental rooms, where temperature, relative humidity and aeration were controlled.…”
Section: Coffee Samplesmentioning
confidence: 99%
“…Drying is one of the post-harvest steps with the most significant influence on coffee quality 19,20 . The coffee drying process reduces the bean's moisture content and prevents the microbial action responsible for spoilage during storage 21 . The drying process of green coffee beans may be accompanied by changes in the physical, chemical, and organoleptic properties of heat-sensitive components 20 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is why the drying process should occur as soon as possible, and it must be duly controlled until the final moisture content is reached. Leading to one issue that the coffee growers face when drying their product since the harvest peaks might overlap with the rainy seasons (García et al, 2014); therefore, the drying process during this time is rather complicated, especially since they tend to sun‐dry the coffee (Firdissa et al, 2022) and the temperature inside the drying facilities highly fluctuate.…”
Section: Introductionmentioning
confidence: 99%
“…The genetic component and cultivation and processing practices significantly impact the physical characteristics and cup quality of coffee [10]. Recent research has shown that the yield, quality, and chemical makeup of Ethiopian coffees are also influenced by the cultivation region [11], environmental factors [12], harvest time [13], and postharvest processing techniques [14,15].…”
Section: Introductionmentioning
confidence: 99%